2004
DOI: 10.1021/jp047590y
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Co+ and Co2+ with Glycine. A Theoretical Study

Abstract: Cobalt cations are open shell systems with several possible electronic states arising from the different occupations of the 3d and 4s orbitals. The influence of these occupations on the relative stability of the coordination modes of the metal cation to glycine has been studied by means of theoretical methods. The structure and vibrational frequencies have been determined using the B3LYP method. Single-point calculations have also been carried out at the CCSD(T) level. The most stable structure of Co(+)-glycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
91
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(99 citation statements)
references
References 77 publications
8
91
0
Order By: Relevance
“…It is seen that four structures (EQ 0 , EQ 1 , EQ 2 , EQ 3 ) are more stable than other structures and have comparable relative energies at this B3LYP/6-31+G(d) level without zero-point correction. This result is in good agreement with previous theoretical studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The EQ 2 structure is stabilized by the presence of the five-membered ring and by attractive electrostatic interactions between K + and negative charges on carboxylic oxygen and the amine nitrogen.…”
Section: Introductionsupporting
confidence: 92%
See 2 more Smart Citations
“…It is seen that four structures (EQ 0 , EQ 1 , EQ 2 , EQ 3 ) are more stable than other structures and have comparable relative energies at this B3LYP/6-31+G(d) level without zero-point correction. This result is in good agreement with previous theoretical studies [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The EQ 2 structure is stabilized by the presence of the five-membered ring and by attractive electrostatic interactions between K + and negative charges on carboxylic oxygen and the amine nitrogen.…”
Section: Introductionsupporting
confidence: 92%
“…In addition, it should be pointed out that the interaction between potassium cation and protein plays an especially important role in the selective transport phenomenon across cell membrane. Although many structures of the glycine-K + complex have been extensively studied in the past, we have also characterized the potential energy surface profile of this system using the GRRM (Global Reaction Route Mapping) computational algorithm [43][44][45][46] (which will be described below in detail), that can automatically find all possible local minima and transition states on a given multi-dimensional potential energy surface, to confirm the previous results [29][30][31][32][33][34][35][36][37][38][39][40][41][42]. Fig.…”
Section: Introductionsupporting
confidence: 65%
See 1 more Smart Citation
“…The structure of glycine cationized with singly charged metal cations has been analyzed in previous theoretical works [13,[31][32][33][34][35][36][37][38][39][40][41][42][43][44]. It has been found that the lowest isomer of cationized glycine is a charge solvated structure.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, extensive studies on gaseous glycine have shown that zwitterions (salt bridge forms) are not even local minima on the potential energy surface of glycine [31,[45][46][47][48][49][50][51][52]. One of the ways to induce the natural to zwitterion transition in the gas phase is favoring the zwitterion by attaching a charged species such as an atomic metal cation [13,32,[34][35][36][37]43,44,53]. Such studies have established that for complexation of glycine by doubly charged cations the salt bridge structure, in which the metal ion interacts with the carboxylate end of zwitterionic glycine, is preferred in most cases.…”
Section: Introductionmentioning
confidence: 99%